Complete mitochondrial genome of the giant root-rat (Tachyoryctes macrocephalus) - Reuber, Victoria M; Rey-Iglesia, Alba; Westbury, Michael V; Cabrera, Andrea A; Farwig, Nina; Skovrind, Mikkel; Šumbera, Radim; Wube, Tilaye; Opgenoorth, Lars; Schabo, Dana G; Lorenzen, Eline D (Mitochondrial DNA. Part B, Resources, 2021)
The endangered giant root-rat (Tachyoryctes macrocephalus, also known as giant mole rat) is a fossorial rodent endemic to the afro-alpine grasslands of the Bale Mountains in Ethiopia. The species is an important ecosystem engineer with the majority of the global population found within 1000 km2. Here, we present the first complete mitochondrial genome of the giant root-rat and the genus Tachyoryctes, recovered using shotgun sequencing and iterative mapping. A phylogenetic analysis including 15 other representatives of the family Spalacidae placed Tachyoryctes as sister genus to Rhizomys with high support. This position is in accordance with a recent study revealing the topology of the Spalacidae family. The full mitochondrial genome of the giant root-rat presents an important resource for further population genetic studies.
Keywords: Tachyoryctes; phylogenetics; Bale Mountains; Mitochondrial genome